Biosynthesis of Self‐Assembled Proteinaceous Nanoparticles for Vaccination. Issue 42 (2nd September 2020) - Pan, Chao; Wu, Jun; Qing, Shuang; Zhang, Xiao; Zhang, Lulu; Yue, Hua; Zeng, Ming; Wang, Bin; Yuan, Zheng; Qiu, Yefeng; Ye, Huahu; Wang, Dongshu; et al.
Abstract: Recent years have seen enormous advances in nanovaccines for both prophylactic and therapeutic applications, but most of these technologies employ chemical or hybrid semi‐biosynthetic production methods. Thus, production of nanovaccines has to date failed to exploit biology‐only processes like complex sequential post‐translational biochemical modifications and scalability, limiting the realization of the initial promise for offering major performance advantages and improved therapeutic outcomes over conventional vaccines. A Nano‐B5 platform for in vivo production of fully protein‐based, self‐assembling, stable nanovaccines bearing diverse antigens including peptides and polysaccharides is presented here. Combined with the self‐assembly capacities of pentamer domains from the bacterial AB5 toxin and unnatural trimer peptides, diverse nanovaccine structures can be produced in common Escherichia coli strains and in attenuated pathogenic strains. Notably, the chassis of these nanovaccines functions as an immunostimulant. After showing excellent lymph node targeting and immunoresponse elicitation and safety performance in both mouse and monkey models, the strong prophylactic effects of these nanovaccines against infection, as well as their efficient therapeutic effects against tumors are further demonstrated. Thus, the Nano‐B5 platform can efficiently combine diverse modular components and antigen cargos to efficiently generate a potentially very large diversity of nanovaccine structures using many bacterial species. Abstract : The Nano‐B5 platform is fully self‐assembled in vivo, and it thus serves as a versatile platform to combine diverse self‐adjuvant modular chassis components and antigens to generate high‐performance nanovaccines. Such a platform can not only display peptide antigens but also polysaccharide antigens. Strong prophylactic effects against infection and efficient therapeutic effect against tumors are demonstrated in various animal models including mice and monkeys.